2020
DOI: 10.1177/2325967120909913
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Magnetic Resonance Imaging for Guiding Tibial and Femoral Tunnel Position in Anterior Cruciate Ligament Reconstruction: A Cadaveric Study

Abstract: Background: Femoral and tibial tunnel malposition for anterior cruciate ligament (ACL) reconstruction (ACLR) is correlated with higher failure rate. Regardless of the surgical technique used to create ACL tunnels, significant mismatches between the native and reconstructed footprints exist. Purpose: To compare the position of tunnels created by a standard technique with the ones created based on preoperative 3-dimensional magnetic resonance imaging (3D MRI) measurements of the ACL anatomic footprint. Study Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…10 It has also been demonstrated that providing femoral footprint coordinates does not improve the precision by which surgeons place the tunnels. 24 In conjunction with the result of the present study, we posit that future work should focus on the implementation of 3D navigation for femoral tunnel placement. This would, in theory, reduce errors introduced by reliance on coordinate measurements transferred from the imaging workstation to the operating room.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…10 It has also been demonstrated that providing femoral footprint coordinates does not improve the precision by which surgeons place the tunnels. 24 In conjunction with the result of the present study, we posit that future work should focus on the implementation of 3D navigation for femoral tunnel placement. This would, in theory, reduce errors introduced by reliance on coordinate measurements transferred from the imaging workstation to the operating room.…”
Section: Discussionmentioning
confidence: 59%
“…26 There is consensus that precise anatomic placement of the ACL femoral graft is of paramount importance in restoring the function and stability of the injured knee. [2][3][4]17,23,24 However, it is also well established that conventional arthroscopic methods of femoral graft localization are lacking with respect to accuracy. 6,13,25,30,37 Recent work has focused on the anatomic reconstruction of the femoral footprint using preoperative imaging as a guide, with various groups utilizing magnetic resonance imaging (MRI) and computed tomography (CT) for femoral footprint characterization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of CT imaging is limited due to the risk of radiation exposure, which can be reduced with low‐dose CT protocols [41, 55]. Alternatively, pre‐operative MRI of the contralateral knee may also be used to locate the anatomic ACL insertion site [33, 46, 51]. But, both 3D‐CT and MRI are costly and may not be readily available.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, 2D and 3D MRI have been used and validated for the evaluation of tunnel shape. 29,31,50 Although MRI may have potential to characterize tunnel size and position, special sequencing is required, and metal artifact may distort images. Nevertheless, advancements in MRI make it a promising emerging modality for comprehensive evaluation of bone tunnels after ACLR without the need for ionizing radiation.…”
Section: Radiographic Evaluation and Classificationmentioning
confidence: 99%